SECURE CRYPTO MODULE INCLUDING OPTICAL SECURITY PATHWAY (2019)
An optical electromagnetic radiation (EM) emitter and receiver are located upon a printed circuit board (PCB) layer and are optically connected to an optical security pathway that is between a pair of signal traces. A predetermined reference flux is determined, the reference flux being the expected EM transmitted by the optical security pathway and received by the receiver. When the PCB is subject to an unauthorized access thereof (e.g., drilled, sawed, cut, etc.), the optical EM transferred by optical security pathway is altered. An optical monitoring device that monitors the flux of the optical EM received by the receiver detects a change in flux, in relation to the reference flux, and passes a tamper signal to one or more computer system devices to respond to the unauthorized access. For example, one or more cryptographic adapter card or computer system functions or secured crypto components may be disabled.